(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2020)
This paper provides a brief synthesis of the evidence and principal points of discussion concerning the indigenous languages of ancient Sicily. Traditionally, three indigenous languages (Sikel, Sikan, and Elymian) are identified in use in Sicily in the period between the seventh and fourth centuries BCE. The evidence is extremely fragmentary, and its study is additionally complicated by the absence of up-to-date systematic collection of the material. The evidence is listed and the key points of linguistic and graphic discussion are presented. The traditional separation of Sikel and Sikan had already been challenged in existing scholarship; this paper suggests, in line with recent work, that the existing assumptions about the separation of Elymian also deserve to be challenged, and that the traditional assumptions about material and/or ethnic cultural boundaries on the island are potentially misleading.